2003
DOI: 10.1586/14760584.2.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Designing pediatric vaccine formularies and pricing pediatric combination vaccines using operations research models and algorithms

Abstract: The National Immunization Program, housed within the Centers for Disease Control and Prevention in the USA, has identified several challenges that must be faced in childhood immunization programs to deliver and procure vaccines that immunize children from the plethora of childhood diseases. The biomedical issues cited include how drug manufacturers can combine and formulate vaccines, how such vaccines are scheduled and administered and how economically sound vaccine procurement can be achieved. This review dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…However, such actions may lead to competing manufacturers exiting the pediatric vaccine market, resulting in a vaccine monopoly that in turn could lead to large price increases in the long term. Given that the federal government purchases 60% of pediatric vaccines in the United States, they are well positioned to prevent such a future situation or crisis [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such actions may lead to competing manufacturers exiting the pediatric vaccine market, resulting in a vaccine monopoly that in turn could lead to large price increases in the long term. Given that the federal government purchases 60% of pediatric vaccines in the United States, they are well positioned to prevent such a future situation or crisis [14].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine selection algorithm can also be used to compare the DTPa-HBV-IPV and DTPa-HIB-IPV vaccines by reverse engineering their prices, both individually and head-to-head. Such information can be of value to both vaccine manufacturers (in anticipating the potential market value for each combination vaccine) and health care providers (in determining which vaccine is of better value for their particular immunization environment, since these two combination vaccines are not designed to be used simultaneously; see [14]) to assess a vaccine's market value. This paper describes how the vaccine selection algorithm can be used to evaluate and compare two partially overlapping combination vaccines (DTPa-HBV-IPV and DTPa-HIB-IPV) for pediatric immunization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts have spanned a broad spectrum of problems, ranging from vaccine procurement and distribution [10], the economic analysis of pediatric vaccine formularies, including the impact of combination vaccines [11,12,21], and vaccine configuration and the design of DNA vaccines [5,9,22]. This paper analyzes the pediatric vaccine stockpile levels proposed by the United States Department of Health and Human Services to determine the risks associated with such levels in the event of vaccine production interruptions.…”
Section: Introductionmentioning
confidence: 99%
“…3 To cut down on vaccination appointments but maintain vaccine take-up, combined vaccines are utilized or co-administration is practiced, with different vaccines given in different parts of the body in one visit. 4 Simultaneous administration is universally recognized as improving vaccination coverage in children as it does not interfere with development of the immune response to the injected antigens, does not significantly increase reactogenicity and does not compromise vaccination safety, [5][6][7] though the effect of simultaneous administration on immune responses is still under debate. In fact some studies have shown that vaccine combination did not decrease immunogenity of single vaccine antigens, but that it could increase the immune response.…”
mentioning
confidence: 99%